1993
DOI: 10.1590/s0074-02761993000100023
|View full text |Cite
|
Sign up to set email alerts
|

An experimental and clinical assay with ketoconazole in the treatment of Chagas disease

Abstract: Ketoconazole, an azole antifungic drug which is already in the market has also been demonstrated to be active against Trypanosoma cruzi experimental infections. In this paper we confirmed the drug effect and investigated its range of activity against different T. cruzi strains naturally resistant or susceptible to both standard drugs Nifurtimox and Benznidazole used clinically in Chagas disease. Moreover, we have shown that the association of Ketoconazole plus Lovastatin (an inhibitor of sterol synthesis), whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 0 publications
2
39
0
2
Order By: Relevance
“…1d) was administered in doses between 3.1 and 8.7 mg/kg by oral route during 51 to 96 days and cure evaluation was performed by hemoculture, conventional serology and complement-mediated lysis. The patients were monitored up to 60 months and it was observed that the drug was unable to erradicate the parasites, from 6 out of 8 patients with positive hemoculture and two others with positive serology (Brener et al 1993).…”
Section: Ketoconazolementioning
confidence: 99%
“…1d) was administered in doses between 3.1 and 8.7 mg/kg by oral route during 51 to 96 days and cure evaluation was performed by hemoculture, conventional serology and complement-mediated lysis. The patients were monitored up to 60 months and it was observed that the drug was unable to erradicate the parasites, from 6 out of 8 patients with positive hemoculture and two others with positive serology (Brener et al 1993).…”
Section: Ketoconazolementioning
confidence: 99%
“…Like many fungi and yeasts, T. cruzi has a strict requirement of specific endogenous sterols for cell viability and growth and is extremely sensitive to sterol biosynthesis inhibitors in vitro (13, 16, 29, 31-33, 35, 36). However, currently available sterol biosynthesis inhibitors, which are highly successful in the treatment of fungal diseases, are not powerful enough to eradicate T. cruzi from experimentally infected animals or human patients (3,18,20). Recent work from our laboratories has shown that new azole derivatives (inhibitors of fungal cytochrome P-450-dependent C 14 sterol demethylase), such as D0870 (Zeneca Pharmaceuticals) and SCH 56592 (Schering-Plough Research Institute, Kenilworth, N.J.), are capable of inducing parasitological cures in murine models of both acute and chronic Chagas' disease (13,29,30,33,34) and are the first compounds ever to display such activity.…”
mentioning
confidence: 99%
“…Although T. cruzi requires specific endogenous sterols for cell viability and proliferation and thus is extremely sensitive to SBI in vitro (reviewed in references 27, 28, and 30), currently available SBI are not powerful enough to eradicate T. cruzi from experimentally infected animals or human patients (4,12,20,22). However, we have recently shown that new triazole derivatives such as D08070 (Zeneca Pharmaceuticals) and SCH 56592 (Schering-Plough), both selective inhibitors of the parasite's sterol C14␣ demethylase with high intrinsic anti-T. cruzi activity and special pharmacokinetic properties (long terminal half-lives and large volumes of distribution), are capable of inducing radical parasitological cure of both acute and chronic experimental Chagas' disease (21,28,30,34,35) (Fig.…”
mentioning
confidence: 99%